PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA PT. MERBAUJAYA INDAHRAYA - Fabian Faqih; Aidin Hudani Awasinombu; Juharsah Juharsah; Endro Sukotjo; Hastuti Hastuti (Jurusan Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Halu Oleo, 2023)
This study aims: (1) To determine simultaneously the effect of transformational leadership and work environment on the performance of employees of PT. Merbaujaya Indahraya. (2) To determine the effect of leadership on the performance of employees of PT. Merbaujaya Indahraya. (3) To determine the effect of the work environment on the performance of employees of PT. Merbaujaya Indahraya. The total population in this study is all employees as many as 60 people who are also used as research samples using purposive sampling technique. This study uses multiple linear regression analysis.The results of the study show that: (1) transformational leadership and work environment have a positive and significant effect on the performance of PT. Merbaujaya Indahraya. (2) transformational leadership has a positive and significant effect on the performance of employees of PT. Merbaujaya Indahraya (3) the work environment has a positive and significant effect on the performance of employees of PT. Merbaujaya Indahraya.